Empirical Legal Research based on Jasser Auda's Maqashid Syariah Theory - Isman; Syamsul Hidayat; Imran Rosyadi; Muhammad Syafri Firman; Nimas Ayu Sholehah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
This research highlights the limitations of the pragmatic paradigm in empirical legal research and offers a conceptual alternative using Jasser Auda's Maqasid Shariah theory. The limitations of the pragmatic paradigm include theoretical constraints, pragmatism, limited method accuracy with data, social reductionism, and weak contextualization of research findings. To address these issues, a hermeneutical approach can be employed, utilizing a more holistic theoretical framework and expanding the scope of pragmatic applications. The historical restructuring and methodological restructuring of the empirical legal research model are carried out through Jasser Auda's Maqasid Shariah theory, providing a broader understanding of legal behavior within social contexts.